Tristan L'Hermite: La Mariane A Critical Analysis - Westgate, David Edward (My University, 1963)
This study gives an appraisal of Tristan L'Hermite's dramatic technique with special reference to La Mariane. It seeks to link the play with the dramatic tend- encies of 1636 and shows that the tragedy played an im- portant role in the popularization and implementation of trends which were to form the basis of the classical system.
Keywords: Tristan L'Hermite; French Literature; La Mariane; French plays